The Kansanshi Cu-Au deposit, Domes region, Zambia : geology, mineralisation and alteration characteristics in the main pit - Chinyuku, Donald Tichaona (Rhodes University, Faculty of Science, Department of Geology, 2014)
The Kansanshi Cu-Au deposit located in the Domes region of the North West province of Zambia is characterised by structurally controlled high angle veins and associated alteration halos. The northwest trending Kansanshi antiform flanks the Solwezi syncline to the north and hosts the Kansanshi deposit and consists of tillites and metasedimentary rocks. Mineralisation is associated with Neoproterozoic Pan African deformation events experienced during the formation of the Lufilian fold belt; however recent findings confirm that structures in the form of reverse and normal faults and drag folds are critical controls on mineralisation within the deposit, Main pit in particular. Low angle faults occurring below the current pit are believed to have served as major fluid pathways during mineralisation. Age dating data from the Kansanshi deposit suggest that mineralisation took place between 512 and 503 Ma indicating that the event was associated with metamorphism. Two types of alteration are dominant within the Main pit (Kansanshi deposit) with the type and intensity of alteration being largely controlled by lithological units. Albite alteration occurs dominantly in phyllites and schists whereas dolomitisation is prevalent in calcareous units. Alteration is associated with mineralisation, and therefore is used as a condition for predicting vein or disseminated mineralisation. The high Au tenor at Kansanshi can be attributed to gold grains occurring in association with melonite (NiTeâ‚‚) and microfractured pyrite intergrown with chalcopyrite in sulphide and quartz dominated veins and veinlets. Analysis of gold grade distribution within the Main pit shows a clear concentration of the element along the major north-south trending structures like the 4800 and 5400 zones, possibly through supergene enrichment in the oxide-transition-sulphide zones. It is imperative that exploration for Kansanshi-type deposits will require geochemical and geophysical studies, understanding of the geology of an area to identify the three lithostratigraphic units (red beds, evaporites and reducing strata).
Keywords: Kansanshi Mine -- Zambia; Copper mines and mining -- Zambia; Gold mines and mining -- Zambia; Gold -- Assaying -- Zambia; Geology -- Zambia; Mineralogy -- Zambia; Tillite